Sara Douda's Essence of Symbols: Expressions of Art, Culture and Faith of the Loli Community West Sumba - Sutomo, Sulistyastuti; Tari, Ezra; Djawa, Maya (Academic Journal of Educational Sciences, 2025)
The Sara Douda dance is a form of oral tradition of cultural arts that combines movement elements from the original dance of the Loli community accompanied by energetic traditional music, namely gongs and drums, as a powerful medium for expressing the experience of faith, namely thanksgiving to the Almighty for giving His grace in the life of Loli society. Sara Douda is full of verbal and non-verbal symbols, rich in meaning, messages and cultural values ​​for the Loli community, used for social interaction and is also an expression of faith to the Highest. To obtain the meaning of symbols in Sara Douda cultural poetry, the author used qualitative methods to search for information related to Sara Douda tradition by conducting interviews in the Tarung-Loli village of West Sumba. The aim of this research is to obtain an overview of the essence, form and meaning of the Sara Douda cultural symbol as a form of expression of art, culture and faith of the Loli people in the study of Contextual Theology with Paul Tillich's perspective which is packaged in the title "Sara Douda Symbol: Expression of Art, Culture and Faith of the Loli Community West Sumba”. Sara Douda is a cultural symbol of the Loli people and also a symbol of their faith. Religious symbols allow individuals to access Divine reality and express their experiences of faith within a cultural context. The verbal and nonverbal symbols in Sara Douda show the Loli Community's faith and belief in God, the Creator of heaven and earth as in the phrase of Ama wolo Ama rawi. Their offerings of praise and expressions of gratitude have been expressed through poetry in the form of couplets and lines as well as beautiful dances from time to time, from generation to generation until now. It can be said that the essence of Sara Douda culture is a means for Loli people to carry out theology contextually in social life.